Use of deep-rooted tropical pastures to build-up an arable layer throught improvement soil properties of an oxisol in the Eastern Plains (Llanos Orientales) of Colombia - Amézquita Collazos, Edgar; Thomas, Richard J.; Rao, Idupulapati M.; Molina López, Diego Luis; Hoyos Garcés, Phanor (2004)
It is widely believed that tropical soils (mainly Oxisols) have excellent physical characteristics such as high infiltration rates, high permeability of water, good and stable soil structure and that consequently, they can support mechanized agriculture. However in the Eastern Plains (Llanos Orientales) of Colombia, when Oxisols are subjected to tillage using disc harrow, soil physical conditions deteriorate rapidly. We report here that change in land use with deep-rooted tropical pastures can enhance soil quality by improving the size and stability of soil aggregates when compared with soils under monocropping. In addition, rates of water infiltration improved by 5-10-fold while rainfall acceptance capacity improved by 3-5-fold. We suggest that intensive and sustainable use of these Oxisols, could only be possible if an arable or productive layer (i.e. a layer with improved soil physical, chemical and biological properties) is constructed and maintained. One option to achieve this arable layer is through the use of introduced tropical pastures with deep-rooting abilities that can result in increased soil organic matter and associated improvements in soil physical, chemical and biological properties. One land use option that can achieve these soil improvements is agropastoralism whereby pastures and crops are grown in short-term rotations.